Profitability Moderates Institutional Ownership’s Impact on Financial Distress: Profitabilitas Memoderasi Dampak Kepemilikan Institusional pada Financial Distress - Betari, Fristia Harum; Hanif, Aisha (Indonesian Journal of Law and Economics Review, 2023)
This study aims to examine the impact of leverage, sales growth, institutional ownership, and profitability on financial distress in the Retail Trade Subsector Companies listed on the Indonesia Stock Exchange between 2017 and 2021, and to investigate the moderating effect of profitability on these relationships. The study uses quantitative analysis and secondary data from financial statements of 18 purposively sampled companies. The Smart Partial Least Square 3.2.7 program was used for statistical analysis. The results indicate that leverage has a significant impact on financial distress, while sales growth and institutional ownership do not affect financial distress. Profitability was found to moderate the relationship between institutional ownership and financial distress. The study provides important insights into factors that contribute to financial distress in this sector, highlighting the moderating role of profitability in managing financial distress. The findings may have practical implications for managers and investors in the Retail Trade Subsector Companies listed on the Indonesia Stock Exchange. Highlights: Leverage has a significant impact on financial distress in the Retail Trade Subsector Companies listed on the Indonesia Stock Exchange. Sales growth and institutional ownership do not have a direct effect on financial distress. Profitability plays a moderating role in the relationship between institutional ownership and financial distress.